Personally salient, emotionally negative task contexts provoke goal neglect in depression. Issue 5 (6th April 2020) - Werner-Seidler, Aliza; Dahm, Theresa; Golden, Ann-Marie; Manly, Tom; Dalgleish, Tim
Abstract: Background: Goal neglect refers to a dissociation between intended and actual action. Although commonly associated with frontal brain damage, this phenomenon is also characteristic of clinical depression. To date, tests of goal neglect typically require individuals to switch between subtasks populated with neutral stimuli. This study examined the impact of affective and personally salient stimulus contexts on goal neglect in clinical depression. Methods: Participants were randomly allocated to either positively or negatively-valenced versions of the Affective Six Elements Test (A-SET). We hypothesised that depressed individuals ( n = 30) would exhibit an overall impairment in A-SET performance by neglecting entire subtasks and allocating suboptimal time to each task, relative to never-depressed peers ( n = 30), with effects being strongest for the negatively-valenced version. Results: Findings showed that depressed individuals exhibited specific deficits, relative to controls on these measures in the negative A-SET only, with a magnitude comparable to that found in brain injured patients. Conclusions: Individuals with depression are impaired in their ability to monitor performance and implement strategies that are optimal for the purpose of pursuing an overarching goal when the task context is negatively-valenced. Potential mechanisms are discussed.